Potential regulatory role of miRNA and mRNA link to metabolism affected by chronic intermittent hypoxia - Duan, Yanru; Zhang, Shihan; Li, Yu; Zhao, Wen; Xie, Pinxue; Zhang, Xi; Du, Yunhui (Frontiers in Genetics, 2022)
Aim Intermittent hypoxia (IH) is the prominent feature of obstructive sleep apnea (OSA) pathophysiology, which is an in dependent risk factor of cardiovascular complications. The effects of IH on adipocyte metabolism were explored by high-throughput sequencing technology. Methods Plasma was collected from OSA patients and control group to perform mRNA sequencing. 3T3-L1 cells were differentiated into adipocytes then subjected to a 5–21% O2 hypoxic environment (IH) for 24 hours. High-throughput sequencing method was used to determine differential mRNA and miRNA patterns in fat cells exposed to IH. We then performed Gene Ontology (GO) analysis, identified relevant KEGG pathways and miRNA-target-pathways. Results Sequencing data showed that OSA affected the expression of 343 mRNAs in the plasma. At the same time, we found that IH affected the expression of 3034 mRNAs in the adipocytes. In addition, 68 differentially expressed mRNAs were overlapped in plasma from OSA patient and IH-induced adipocyte model. we observe that 68 differential genes could be connected to 49 reciprocally expressed miRNAs. we showed that IH significantly reduced the expression of miR-182-5p and miR-30c-2-3p. KEGG predicted that the function of expressed miR-182-5p and miR-30c-2-3p was enriched to AKT signaling pathway. Notably, IH activated PI3K/AKT pathway in fat cells. Conclusion Our results demonstrated that IH may induce adipocyte metabolism by regulating miR-182-5p and miR-30c-2-3p.